The Effect of Levothyroxine in Comparison with Placebo on Serum Osteocalcin Levels in Patients with Subclinical Hypothyroidism - Rezaee, Reihaneh; Mohebbi, Masoud; Afkhamizadeh, Mozhgan; Yaghoubi, Mohammad A.; Hoseinzadeh, Mansoureh; Najafi, Mona Najaf; Sahebkar, Amirhossein (Current Drug Safety, 2022)
Background and Objective: Subclinical hypothyroidism can potentially develop into overt hypothyroidism. Thyroid hormones have substantial roles in metabolism and glucose homeostasis and thus, are closely related to determinant factors of metabolic syndromes, such as obesity and insulin resistance. Osteocalcin is considered a predictor of metabolic conditions in thyroid diseases. This study aimed to investigate the effect of levothyroxine vs. placebo on serum osteocalcin levels in patients with subclinical hypothyroidism. Methods: This randomized clinical trial was performed on 30 patients with subclinical hypothyroidism, who were referred to the endocrine clinics of Ghaem and Imam Reza hospitals in Mashhad, Iran. After giving informed consent, patients were randomly divided into intervention (50 μg/- day levothyroxine for 2 months) and control (placebo) groups. Serum levels of osteocalcin, thyroid hormones, lipid profile, insulin, and fasting glucose, as well as other clinical and anthropometric data, were measured at baseline and at the end of the study. SPSS was used to analyze the data, and p < 0.05 was considered significant. Results: Mean age in the intervention and control groups was 35.07 ± 9.94 and 31.30 ± 4.30, respectively (p = 0.20). There was no significant difference between osteocalcin levels before and after the intervention in either of the groups (p = 0.54). TSH level was significantly decreased in the levothyroxine group after the intervention (p < 0.01). T4 level was significantly increased in the intervention group (p = 0.02). Conclusion: Levothyroxine had no significant effect on the increasing levels of serum osteocalcin in patients with subclinical hypothyroidism.
Keywords: insulin resistance